NMR study of proton dynamics in ferroelectric KIO₃*2HIO₃ crystal - Baisa, D.F.; Chesnokov, E.D.; Ovcharenko, A.I.; Vertegel, I.G. (Functional Materials, 2008)
The temperature dependence of the proton spin-lattice relaxation time T₁ has been studied in ferroelectric KIO₃*2HIO₃ crystal. It is shown that the proton jumping along 0—H....0 contact has been shown to be the main relaxation mechanism. At temperatures exceeding the phase transition one, e>Tc, the proton relaxation is caused by the motion thereof in symmetric two-well potential of the hydrogen bond with activation energy Ec = 3.4 kcal/mol. At T<Tc, the proton ordering in asymmetric two-well potential occurs with activation energies Ea1 = 4.1 kcal/mol and Ea2 = 2.5 kcal/mol. Evaluation of equilibrium constant value a = p₁/p₁, where p₁ and p₁ are the probabilities of proton being in position "1" or "2" of double-well potential near Tc, gives the value a≈40, but yet at Tc,—T ≈ 50 K, a≈450, thus evidencing a high proton ordering degree on H-bond below the phase transition.